Expected Asylum Seekers and Far-Right Voting: Effects of a Dispersal Act - Joop Age Harm Adema (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Far-right parties frequently mobilize anti-refugee sentiment during periods of high asylum migration. Prior work shows that exposure to transit routes and regional inflows tends to raise far-right support, whereas direct local contact with asylum seekers can dampen it. Yet much of the sharp rise in far-right voting around major refugee waves remains unexplained by actual inflows. I study a Dutch policy reform, the Dispersal Act, which obligated municipalities to host asylum seekers and thereby generated a sudden, plausibly exogenous increase in expected future local inflows. Comparing changes in far-right vote shares between not-yet and already hosting municipalities before the actual arrival of asylum seekers allows me to isolate the electoral effect of heightened expectations of future hosting. I find that affected municipalities experienced a substantial increase in far-right support following the Act's passage. The effect operates on both the extensive margin (whether municipalities expect to host) and the intensive margin (how many they expect to host): a one-percentage-point increase in allocated asylum-seeker share raises far-right vote shares by about 1.2 percentage points.
Keywords: D72; F22; H75; 330; asylum seekers; far-right voting; group threat; migration